Kontribusi Perhatian Orangtua Dan Lingkungan SosialTerhadap Aktivitas Belajar Siswa Dan Dampaknya PadaHasil Belajar Matematika Siswa Kelas VII Semester GenapSMP Muhammadiyah 6 Surakarta Tahun Ajaran 2015/2016 - , Dita, Dra. Sri Sutarni, M. Pd (2016)
The aimed of research this to analyze and examine are: (1) The contribution of attention parents and social environment indirect toward mathematics learning outcomes through learning activities, (2) The contribution of attention parents and social environment direct toward learning activities, (3) The contribution of learning activities on real toward mathematics learning outcomes. The type of the research is quantitative research. The population of the research is all of student seventh grade at SMP Muhammadiyah 6 Surakarta. The sample of the research a number of 79 student. The technique of collecting data with methods of questionnaire and documentation. The technique of analyzing data by using path analysis. The finding of the research with α = 5 %: (1) There is contribution of attention parents and social environment indirect toward mathematics learning outcomes through learning activities, (2) There is contribution of attention parents and social environment direct toward learning activities, (3) There is contribution of learning activities on real toward mathematics learning outcomes.